2016
DOI: 10.1097/coh.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from acute HIV infection

Abstract: Purpose of reviewUnderstanding the characteristics of transmission during acute HIV infection (AHI) may inform targets for vaccine-induced immune interdiction. Individuals treated in AHI with a small HIV reservoir size may be ideal candidates for therapeutic HIV vaccines aiming for HIV remission (i.e. viremic control after treatment interruption).Recent findingsThe AHI period is brief and peak viremia predicts a viral set point that occurs 4–5 weeks following infection. Robust HIV-specific CD8+ T-cell response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 41 publications
0
41
0
1
Order By: Relevance
“…Primary HIV infection (PHI) is a crucial phase of HIV infection with a limited window of opportunity . A prompt antiretroviral treatment (combined antiretroviral therapy [cART]) initiation it is able to lead to a reduction of HIV reservoir, to a better immunological recovery and to a reduction of onward HIV transmission . Consequently, it is mandatory to start cART as soon as possible according to the current guidelines during PHI .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary HIV infection (PHI) is a crucial phase of HIV infection with a limited window of opportunity . A prompt antiretroviral treatment (combined antiretroviral therapy [cART]) initiation it is able to lead to a reduction of HIV reservoir, to a better immunological recovery and to a reduction of onward HIV transmission . Consequently, it is mandatory to start cART as soon as possible according to the current guidelines during PHI .…”
Section: Introductionmentioning
confidence: 99%
“…to a reduction of onward HIV transmission. 2,3 Consequently, it is mandatory to start cART as soon as possible according to the current guidelines during PHI. 4 Nevertheless, the assessment of drug resistance before treatment initiation is crucial because suboptimal cART could lead to increased risk of virological failure.…”
mentioning
confidence: 99%
“…Many patients experience a variety of non-specific flu-like symptoms in this phase, which bear resemblance to mononucleosis-like syndrome. During this time, patients have significantly elevated HIV burden in the plasma and genital secretions, thus increasing the likelihood of transmission [9,10]. According to the commonly employed Fiebig staging classification system for HIV infection, acutely infected patients do not have any detectable HIV antibodies (Fiebig stages 1 to 2).…”
Section: Introductionmentioning
confidence: 99%
“…These reservoirs usually reach a set point within the first two months of infection and serve as predictors of long term HIV control [10] [24]. When ART is discontinued, these HIV latent reservoirs allow for viral rebound to occur [25] [26].…”
Section: Introductionmentioning
confidence: 99%
“…Since HIV-specific antibodies were found to correlate with reduced HIV acquisition in the RV144 vaccine trial, which showed 31% efficacy (2), induction of humoral responses has been the primary outcome pursued in HIV vaccine trial design. Nevertheless, T-cell responses are considered likely to contribute to viral control (3) and to prevention of infection from becoming established (4,5). Polyfunctional T cells have been associated with decreased risk of HIV infection in follow-up analyses of the RV144 trial, which identified highly polyfunctional CD4 ϩ T cells expressing CD40L, interleukin-2 (IL-2), IL-4, gamma interferon (IFN-␥), and tumor necrosis factor alpha (TNF-␣) as an additional inverse correlate of infection risk (6), as well as in the HIV Vaccine Trials Network (HVTN) 505 vaccine trial, which identified polyfunctional CD8 ϩ T cells expressing IL-2, IFN-␥, TNF-␣, and granzyme B as an additional inverse correlate of infection risk.…”
mentioning
confidence: 99%